MELIHAT SYAHRUR MENGINTIP AURAT PEREMPUAN - Munawir Munawir (Yinyang: Jurnal Studi Islam Gender dan Anak, 2011)
Abstract: Command closes the nakedness is of religion, but the limitations on the genitalia are influenced by considerations of humanity in all its aspects. For that, thinking about flexibility Sahrur female genitalia (had al-A’la and Hadd al-adna) finds relevance once again so it is important in determining the limit of female genitalis (read: male genitalia as well) the existence of certain mechaniscms of accommodative and responsive against all the values developed in the community. As to the possibility of the existence of pornography porno action and flexibility of this concept of privates parts, then it had to be escorted to the moral education of every layer of society. Keywords: Syahrur, Aurat